Armas, palavras, autonomias: o complexo repertório de confronto do Exército Zapatista de Libertação Nacional (1983-2005) - Julia Melo Azevedo Cruz (2017)
This work seeks to analyze the main strategies of political action employed by the Zapatista Army of National Liberation (EZLN), a Mexican indigenous movement that emerged in the 1980s and struggles mainly for indigenous rights and against the effects of neoliberal globalization. The EZLN has a wide range of ways of acting, mixing armed struggle, actions commonly used by social movements and autonomic strategy through the creation of autonomous indigenous territories, located in the state of Chiapas and controlled by the Zapatistas. We aim to analyze these three groups of performances, seeking to understand the choice for each one of them, the changes they have undergone, their aspects of continuity and innovation in relation to the ways of acting of other groups and their characteristics in general. In addition, we seek to comprehend how the Zapatista political action is based in different sources, dialogues with different audiences, struggles on several fronts and transforms itself when necessary. In this work, we use as source the documents written by the Zapatistas and published on their website. Our time frame approaches the period between 1983, the year of emergence of the EZLN, and 2005, the moment when the group's speeches and political action strategies underwent important changes and a new phase of the Zapatista resistance began, focused on the action called La Otra Campaña, which is not investigated in this work.